Chronic Intake of Green Propolis Negatively Affecting the Rat Testis - Severi-Aguiar, Grasiela Dias de Campos (Pharmacognosy Res, 2017)
BACKGROUND: Human and animal evidence suggests that environmental toxicants may have an adverse impact on male reproductive health, reducing the population's reproductive output. Owing to the renewed attraction for natural products, some of them constitute effective alternatives to mitigate these effects. Propolis is a candidate for this use because of its intrinsic properties. In many situations, it improved the testicular damage and alleviated the toxic effects induced by environmental contaminant exposure. OBJECTIVE: The aim of this study was to investigate possible alterations of testicular parameters and certify if its use is really advantageous to the testis, since this could affect rat reproductive function. MATERIALS AND METHODS: Forty-eight adult male Wistar rats were divided into four groups (Co = control, T1 = 3 mg propolis/kg/day, T2 = 6 mg/kg/day, T3 = 10 mg/kg/day) and were exposed during 56 days. The testes were assessed with morphometrical, stereological, and ultrastructural analyses. Cell proliferation and death were diagnosed, respectively, by immunocytochemistry. Connexin 43 (Cx43) and N-cadherin transcript levels were determined by reverse transcription-polymerase chain reaction. RESULTS: Increased cell proliferation and Leydig cell volume were observed in T2, and in contrast, Cx43 upregulation and cell death were observed in T3. Both T2 and T3 showed ultrastructural abnormalities in testicular parenchyma. CONCLUSION: We recommend a cautious intake of propolis to avoid deleterious effects. SUMMARY: Chronic intake of Brazilian green propolis induced N.-cadherin downregulation and decreased on seminiferous tubule volume. Increase on connexin 43 expression and cell death and decrease in Leydig cell.(LC) number/testis with the concentration of 10 mg/kg/day were observed. Increase on cell proliferation, cytoplasmic proportion, and volume of LC with the concentration of 6 mg/kg/day was detected. The presence of empty spaces between spermatids and malformed spermatozoa in the lumen of seminiferous tubule was showed. This male reproductive disruption can be linked to phenolic compounds present in Brazilian green propolis. [Image: see text] Abbreviation Used: AEC: 3-amino-9-ethylcarbazole; AJ: Adherens junction; AME: Aromadendrin-40-methyl ether; CAPE: Caffeic acid phenethyl ester; Co: Control group; C×43: Connexin 43; DAB: Diaminobenzidine; dNTP: Deoxyribonucleotide phosphate; DSP: Daily sperm production; FA: Ferulic acid; FSH: Follicle-stimulating hormone; GJ: Gap junction; GJIC: Gap junction intercellular communication; HPLC: High-performance liquid chromatography; LC: Leydig cell; LH: Luteinizing hormone; N-cad: N-cadherin; PCNA: Proliferating cell nuclear antigen; PCR: Polymerase chain reaction; RT-PCR: Reverse transcription-polymerase chain reaction; SDM: Standard deviation of mean; T1: Group exposed to 3 mg of propolis/kg/day; T2: Group exposed to 6 mg of propolis/kg/day; T3: Group exposed to 10 mg of propolis/kg/day; TUNEL: Terminal deoxynucleotidyl transferase-mediated dUTP nick-end labeling; WB-ras 2 cells: Ras-transformed rat liver epithelial cell line.